PENGARUH VARIASI KONSENTRASI KOH TERHADAP SIFAT FISIK SABUN CAIR EKSTRAK DAUN PEPAYA (Carica papaya L.) - Dewi Riskha Nurmalasari (AKADEMI FARMASI JEMBER, 2023)
Acne is a skin disease disorder that is often experienced by some people, excess oil on the skin can cause infection and inflammation caused by the development of acne bacteria such as Staphylococcus aureus, Staphylococcus epidermidis, Propionibacterium acnes. The purpose of this study was to determine the effect of variations in KOH concentration on the physical properties of papaya leaf extract liquid soap preparations (Carica papaya L.). The research design used was a pre-experimental research design with one group post-design, using research objects as many as 3 sample treatment groups (variations in KOH concentration 14%; 16%; 18%) as sample research objects. The results of organoleptic tests show that variations in KOH concentration affect the physical properties of organoleptic, texture, and aroma. The homogeneity test results of the three formulas show homogeneous results. The results of the pH test using statistical tests using the One Way ANOVA method obtained a significant value of 0.000 (p-value 0.05). The viscosity test results using the One Way ANOVA method obtained a significant value of 0.000 (p value0.05). The results of the foam height test using the One Way ANOVA method obtained a significant value of 0.006 (p value0.05). Based on the research that has been done, it can be concluded that KOH affects the physical properties of soap, namely organoleptic tests, pH, viscosity, and foam height. Keywords: Liquid Soap, Potassium Hydroxide, Physical Properties